Surgical management of intraosseous compound odontome preserving permanent incisors - report of two cases - S. Juneja; K.G. Verma; N. Singh; S. Jindal (Nigerian Dental Association, 2014)
Odontomas are considered to be hamartomatous malformations rather than tumours. Compound odontomas are mostly found in anterior maxilla and complex odontomas are more prevalent in posterior mandible. Although the pathology is benign, early intervention is required to avoid the subsequent complications and ensure a better prognosis. Two case reports are presented where compound odontomas were associated with impacted teeth. In the first case, an unusually giant odontome caused impaction of both central and lateral incisor. Combined surgical and orthodontic treatment was required for eruption of central incisor whereas lateral incisor erupted after surgical exposure. In the second case surgical removal of the odontome and exposure of the incisal edge led to eruption of the impacted incisor.